Effect of Red Light on the Phototropic Sensitivity of Corn Coleoptiles - Chon, Hyangju P. (1966)
The effect of red light in alteration of the phototropic sensitivity of corn coleoptiles (Zea mays L., cultivar Burpee Barbecue Hybrid) is investigated. Phototropic dosage-response curves for etiolated coleoptiles are compared with those for coleoptiles receiving 1 hour of continuous red light immediately prior to phototropic induction. In the former case, only curvature comparable to the first positive curvature of oat coleoptiles is obtained. There is no evidence for first negative curvature and only minimal second positive curvature. The reciprocity law proved valid for all curvatures obtained. With red light, the sensitivity of the first positive curvature was decreased over ten-fold and there was clear appearance of second positive curvature for which the reciprocity law was not valid. Once again there was no evidence for negative curvature. Time course studies indicated that within 1 hour of the beginning of red light treatment at 25°, reactions leading to the decrease in phototropic sensitivity of the first positive component had gone to completion whether the red light was continuous or consisted of a single 1 second exposure followed by a 1 hour dark period. An action spectrum for the red-induced change in phototropic sensitivity showed a marked peak near 660 mμ with a small broad shoulder between 610 and 630 mμ, characteristic of phytochrome-mediated responses. The effect of red light could be fully reversed by low dosages of far-red light, but longer doses of far red were less effective. Large dosages of far-red light alone induced the same alteration in phototropic sensitivity as did red light.